2018
DOI: 10.1787/f5bd9e57-en
|View full text |Cite
|
Sign up to set email alerts
|

The science of teaching science

Abstract: OECD EDUCATION WORKING PAPERS SERIES OECD Working Papers should not be reported as representing the official views of the OECD or of its member countries. The opinions expressed and arguments employed herein are those of the authors. Working Papers describe preliminary results or research in progress by the authors and are published to stimulate discussion on a broad range of issues on which the OECD works. Comments on Working Papers are welcome, and may be sent to the Directorate for Education and Skills, OEC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…Provision of adequate feedback encapsulates the amount of feedback and advice given to students. These outcomes in the context of PISA 2015 are important because there is evidence to suggest that adaptive teaching and teacher feedback are related with science performance [ 29 ]. Furthermore, these outcomes have been shown to capture meaningful variation in teaching quality and to correlate with students’ intrinsic motivations in terms of predictive validity [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…Provision of adequate feedback encapsulates the amount of feedback and advice given to students. These outcomes in the context of PISA 2015 are important because there is evidence to suggest that adaptive teaching and teacher feedback are related with science performance [ 29 ]. Furthermore, these outcomes have been shown to capture meaningful variation in teaching quality and to correlate with students’ intrinsic motivations in terms of predictive validity [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…Several international reports and projects have recommended that the inquiry process becomes the backbone of teaching, under the common name of inquiry-based science education (IBSE). Numerous quantitative studies have shown the effectiveness limited of non-guidance IBSE and the benefits of guidance IBSE in learning scientific skills [76][77][78][79][80][81]. Furthermore, IBSE engages students in learning [82,83], enhancing their attitudes, motivation, interest, self-confidence, and expectations for the future [33].…”
Section: Scientific Practices For Knowledge Buildingmentioning
confidence: 99%
“…Furthermore, IBSE engages students in learning [82,83], enhancing their attitudes, motivation, interest, self-confidence, and expectations for the future [33]. A necessary benefit of using IBSE as a teaching approach is it promotes the commitment of girls to science and scientific professions [76][77][78][79].…”
Section: Scientific Practices For Knowledge Buildingmentioning
confidence: 99%
“…Previous analyses of PISA data have shown that teachers in mathematics and science across the globe vary considerably in what they teach and, more importantly, in how they teach (Echazarra et al, 2016;Mostafa, Echazarra and Guillou, 2018). To determine how language-of-instruction teachers teach, PISA 2018 asked students several questions about the type of strategies their teachers use in their lessons.…”
Section: Teaching Strategiesmentioning
confidence: 99%